The Amount of Fish Consumption of Vulnerable People Tamannyeleng Village, Barombong District, Gowa Regency - Fawaid, Rezki Inta; Wahid, Abdul; Amri, Andi; Arief, Andi Adri; Firman, Firman; Mustafa, Muhammad Dalvi (PONGGAWA : Journal of Fisheries Socio-Economic, 2024)
The purpose of this study was to determine the number and factors that influence fish consumption in Tamannyeleng Village, Barombong District, Gowa Regency. This research was conducted from June to July 2021 in Tamannyeleng Village, Barombong District, Gowa Regency.   The type of research used is a type of survey, which is research that takes samples from a population in the field and is used as basic data. The sampling technique used is non probability sampling. The technique of non-probability sampling is that each member of the population has zero chance. That is, sampling is based on certain criteria such as judgment, status, quantity, voluntariness and so on. The results of the study obtained were the amount of fish consumption before Covid-19 and after Covid-19 there was a difference. Before the existence of COVID-19, there were several who consumed fish as much as 0.5 kg per week, 1 kg per week, 2 kg per week and there were respondents who no longer consumed fish per week during Covid-19. It can be seen that the people of Tamannyeleng Village feel that during this Covid-19 period they are experiencing difficulties. Meanwhile, the factors that affect fish consumption of vulnerable people in Tamannyeleng Village, Barombong District, Gowa Regency consist of income, education, taste, number of family members, fish prices and fish substitution prices.